Small Stem Exeter Total Hip Replacement: Clinical and Radiological Follow-up over a Minimum of 2.5 Years - S Sivananthan; M Arif; DSK Choon (Journal of Orthopaedic Surgery, 2003)
Purpose. To evaluate the clinical and radiological outcome in patients undergoing small stem Exeter total hip replacement. Methods. A total of 46 small stem Exeter total hip replacements were performed on 44 consecutive patients (18 men and 26 women) attending the University of Malaya Medical Centre. The mean age at the time of operation was 58 years (range, 24–81 years). Of the 46 procedures performed, 35 were primary total hip replacements and 11 were revision operations, with aseptic loosening of the original implant being the main indication for revision. The main indications for surgery in primary cases were avascular necrosis and rheumatoid arthritis. Clinical and radiographic outcomes were assessed at 6 weeks', 12 weeks', 6 months' follow-up, and annually thereafter. Postoperative cementing technique was also assessed. Results. The mean follow-up period was 4 years. The mean Oxford Hip Score improved from 46 points preoperatively to 17 points at the final follow-up examination. There were no revision operations, no implant breakages, and no excessive migration of the implants. The potential complications of implant failure due to smaller implant size and increased patient activity were not observed. Conclusion. Due to the smaller size of Asian femora, the small stem Exeter implant is a very useful development. This study suggests that it will perform as well as its larger counterparts.